Elimination trial of Cedrus deodara Loud.and Cedrus atlantica Manetti. in Chamestan region - Sayyed Ehsan Sadati; Sayyed Reza Mostafanejad (تحقیقات جنگل و صنوبر ایران, 2009)
Elimination trials of exotic species are important for afforestation and reforestation projects. For this purpose, Cedrus atlantica and Cedrus deodara seedlings were planted in 1983 and 1992 in Chamestan region and adaptation of them were studied in 2005. Results showed that the survival of Cedrus deodara (97%) is more than that of Cedrus atlantica (67%). The mean diameter and mean annual diameter increment of Atlas cedar were 28.8cm and 1.1cm, respectively, while those of Deodar cedar were 16.8cm and 1.2cm, respectively. The mean height and mean annual height increment of Deodar cedar were 13.8m and 0.9m, respectively, while those of Atlas cedar were 14.8m and 0.6m, respectively. The volume of Deodar cedar and Atlas cedar were 208 silve ha-1 and 80 silve ha-1, respectively. Besides, the qualitative characteristics of Deodar cedar was better than Atlas cedar. Therefore, this research indicated that Cedrus deodara is more adaptable than Cedrus atlantica in Chamestan region.